“TATARS” AND THE “STATE OF THE TATARS” IN OLD NORSE-ICELANDIC LITERATURE - Jackson T.N.; Litovskikh E.V. (Золотоордынское обозрение)
Research objective: The purpose of this study is to present the entire body of information about the Tatars and the Tatar State contained in Old Norse-Icelandic literature.Research materials: The materials are the works of Old Norse-Icelandic writing of various genres. These are Icelandic annals, geographical treatises, and sagas of several types: chi-valric sagas, bishops’ sagas, sagas of ancient times, and local, or original, chivalric sagas.Results and scientific novelty: An exhaustive selection of source material has been achieved for the first time in scholarly literature. The main conclusion of the study is that there is no single image of the Tatar State in the sources under discussion. The kings’ and bishops’ sagas record real historical events, although they describe them in the style of a saga narrative. The Icelandic annals also reflect actual events, information about which could have been obtained from the works of European chroniclers, gleaned from oral information circulated in Icelandic-Norwegian clerical circles, or even be the result of rumours brought from Europe to the Scandinavian North by pilgrims returning home. In contrast, the authors of the sagas of ancient times and local knights’ sagas create geographical descriptions as a background for their fictional narratives, built on the basis of the knowledge and ideas that the authors themselves possessed and that their Icelandic audience must have had by the mid-13th century. All sources clearly maintain the assignment of the Tatar State to the Eastern quarter of the ecumene within which (like everything little known and dangerous) it was shifted towards the north. In addition, its connection with the Old Russian state, recorded by the sources, can be traced. Despite the fantastic character of the mental map reflected in the later sagas, they have preserved valuable indirect information, namely on the knowledge of the fact that Rus’ happened to be under the rule of the Golden Horde, and the idea of the real geographical position of the Tatar State in the distant parts of the Eastern quarter of the world.